PERMASALAHAN IMAN: KRITIK ATAS IMAN DALAM FILSAFAT BARAT DAN TAWARAN JAWABAN - Wibowo, Setyo (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2013)
Faith becomes problematic in our modern world. In the age of secularization and emancipation man masters the Nature with his growing reason and ever developing technology. This new situation brings with itself a discredit toward faith and religion. Without refusing the existence of God, Immanuel Kant declares that theology is a paralogism (a fallacious reasoning). Auguste Comte corners the religion in the realm of infantile age to be overcomed by the progress of science. Meanwhile Friedrich Nietzsche, from his own view, analyses that the phenomenon of fanatism in religion hides the uncontrallble â€œneed to believeâ€ typically found among the weaks.The central critique of Martin Heidegger toward ontotheological metaphysics shows that theology defi ned as science does not think. Man of faith has already all the answer before a question is posed, therefore he cannot truly pariticipate in the question of Being. This article tries to consider these objections against faith. As an answer, this article off ers to acknowledge â€œthe act of believeâ€ as an universal disposition in man. Much wider than his need to possess knowledge, man is driven by a desire for the infi nite. Faith resumes this human desire for infinite.